Enablers and Barriers to Implement Covid-19 Measures in Long-Term Care Facilities: A Mixed Methods Implementation Science Assessment in Chile - Villalobos-Dintrans, P (LSE Press, 2021)
Background: As elsewhere, in Chile the COVID-19 affected disproportionately older people, and particularly people living in long-term care facilities. Considering this problem, the Government issued a series of guidelines and protocols to prevent and manage COVID-19 outbreaks in these facilities. Methods: This study aims to identify barriers and enablers that affect the implementation of these prevention and management measures. For the analysis, we used an implementation science approach and a mixed methods strategy — a survey among facilities’ managers and interviews among staff — classifying enablers and barriers into four categories: agreement with the intervention’s goals, financial resources to implement the measures, technical needs of the intervention, and cultural factors in the facilities. Results: Results highlight the importance of the four factors above in the implementation of COVID-19 guidelines and protocols. Managers and staff differ in their view of the main enablers and barriers for implementation. However, they both identify the knowledge about the measures and availability of personal protective equipment as enablers and human resources as a potential barrier. Conclusions: The identification of several factors related to goals and culture highlights the need to adopt a broad implementation approach when designing interventions for long-term care facilities, avoid-ing restricting the discussion to the availability of resources. Highlight: • Understanding implementation factors is key to design and assess successful interventions. • The prevention and management measures implemented in the Chilean facilities found barriers (e.g., infrastructure, human capital and resistance to chance), and enablers (e.g., PPE availability and trust in technical staff) that could have impacted the effectiveness of the measures proposed. • Tackling the identified implementation barriers using feasible and evidence based strategies could improve the effectiveness of the measures. © 2021 The Author(s).